Mobile Application for Simulation of Camera Shot Angles Using 3D Environment Virtual Reality - Kurniawan, Ady Purna; Putra, Asaas; Putri, Sritenaya Geovani; Apriliani, Sani (School of Applied Science, Telkom University, 2023)
This paper addresses the challenges faced by Telkom University in online learning, specifically in practical courses that require hardware. One such course is Videography in the Communication Science Study Program, which aims to equip students with theoretical knowledge and practical techniques for shooting from specific angles or positions using camera devices. To overcome this challenge, the study focuses on developing an Android mobile application that simulates the practical exercises in the Camera Shot Angles course. The application utilizes a virtual 3D environment and offers a VR (Virtual Reality) mode, allowing students to immerse themselves in realistic shooting experiences from various positions and angles. It also includes a comprehensive set of questions to evaluate students' understanding of the course material. The testing results indicate that the application is compatible with mobile devices with a minimum of 4GB RAM and has received positive scores for user experience aspects such as attractiveness, perspicuity, and efficiency. This paper discusses the development process, features, and evaluation of the application, highlighting its potential to enhance the practical learning experience for students in the Communication Science Study Program at Telkom University. By providing a virtual platform for practicing camera shot angles, this application offers a solution to the hardware limitations faced during online learning, enabling students to gain practical skills and knowledge effectively.